Pyrophosphate-ferric manganese phosphate sodium composite material and preparation method and application thereof
By introducing trivalent transition metal salt into the positive electrode material of ferrophosphate and in situ coated by sodium ferrophosphate, a composite of ferrophosphate manganese phosphate with high structural stability and excellent electrochemical performance was prepared. Materials solve the problems of low capacity performance and instability of materials in the prior art.
Patent Information
- Application Number
- CN202411612362.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the capacity performance of the cathode material of ferroferric manganese phosphate is low, resulting in limited space for energy density improvement, and the material has problems such as phase change instability and transition manganese dissolution during the circulation process, affecting its application.
By introducing trivalent transition metal salt into the positive electrode material of ferrophosphate pyrophosphate, and using the in-situ coating method of sodium ferrophosphate, a in-situ coating of sodium ferrophosphate was prepared. This method introduces trivalent transition metal elements during the sintering process, changes the element ratio of the material, generates a new phase of NaFePO4, and improves the structural stability and electrochemical properties of the material.
This composite material not only solves problems such as phase change in the raw material and manganese ion dissolution, but also improves the discharge specific capacity, and enhances the electrochemical capacity of the material through the coating of sodium iron phosphate, providing a higher capacity retention rate.
Smart Images

Figure CN119480991A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of positive electrode materials, and in particular to a sodium manganese iron pyrophosphate composite material and a preparation method and application thereof. Background Art
[0002] With the growing demand for large-scale energy storage, the market has high hopes for sustainable and cost-effective battery technology. Currently, lithium-ion batteries (LIBs) are widely adopted due to their high energy density and stable performance, but their dependence on limited lithium resources has raised many concerns. The high cost of lithium resources and the concentrated geographical distribution have led to challenges in the stability of the supply chain and long-term resource availability. In response to these limitations, sodium-ion batteries (NIBs) have gradually attracted attention as a potential alternative. Among them, iron-based phosphate polyanion compounds have attracted much attention because of their stable structure, abundant resources, and are very suitable for large-scale energy storage applications. They are considered to be ideal cathode materials for sodium-ion batteries.
[0003] Na4Fe3(PO4)2(P2O7)(NFPP) is a representative material with a high theoretical capacity (129 mAhg -1 ), and the synthesis process is simple, the cost is low, the cycle life is long, and it has good commercial prospects. However, due to the low working voltage of NFPP, the room for further improvement of battery energy density is extremely limited. How to further improve its energy density has become the research focus of sodium iron pyrophosphate modification. LiFePO4 (LFP) is prepared by replacing iron with manganese to prepare LiMn x Fe 1-x PO4(LMFP) achieves higher working voltage and energy density. However, due to the poor kinetics of manganese, in Na4Mn 1.5 Fe 1.5 (PO4)2(P2O7)(NMFPP) generally exhibits lower capacity and poorer rate performance, further reducing its overall energy density. 3+ It will be affected by the Jahn-Teller effect, causing irreversible phase changes in the crystal structure, compressing the sodium deintercalation channel, and causing some manganese ions to undergo disproportionate reactions and dissolve in the electrolyte, resulting in poor cycle performance of the material.
[0004] Related technologies usually use a solid-phase coating strategy to coat the surface of NMFPP. However, the cost of coating graphene oxide as a carbon coating is too high, and general coating will sacrifice the discharge capacity of the material and cause a loss of energy density, which greatly affects its practical application.
[0005] How to improve the low capacity performance of sodium manganese iron pyrophosphate positive electrode material is a technical problem that needs to be solved by the existing technology. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies, provide a sodium manganese iron pyrophosphate composite material and a preparation method and application thereof, and solve the technical problem of how to improve the low capacity of the sodium manganese iron pyrophosphate positive electrode material in the prior art.
[0007] In order to achieve the above technical objectives, the technical solution of the present invention provides a sodium manganese iron pyrophosphate composite material and a preparation method and application thereof.
[0008] The present invention provides a method for preparing a sodium manganese iron pyrophosphate composite material, comprising the following steps:
[0009] S1, mixing and stirring the sodium manganese iron pyrophosphate positive electrode material, metal salt and solvent to obtain a mixed slurry;
[0010] S2, drying the mixed slurry to obtain powder, and then heating the powder to 600-700° C. in a hydrogen-argon mixed gas atmosphere and keeping the temperature to obtain the sodium manganese iron pyrophosphate composite material.
[0011] In any embodiment, in step S1, the material ratio of the sodium manganese iron pyrophosphate positive electrode material and the metal salt is 10g:(0.01-0.15)mol.
[0012] In any embodiment, the trivalent transition metal salt is one or more of aluminum nitrate, lanthanum nitrate and cerium nitrate.
[0013] In any embodiment, the trivalent transition metal salt is a mixed metal salt of aluminum nitrate, lanthanum nitrate and cerium nitrate.
[0014] In any embodiment, the molar ratio of the aluminum nitrate, the lanthanum nitrate and the cerium nitrate is 1:(1-1.5):(1-1.5).
[0015] In any embodiment, in step S1, the solvent is ethanol.
[0016] In any embodiment, in step S1, the mixing and stirring speed is 300-400 r / min, and the mixing and stirring time is 2-3 h.
[0017] In any embodiment, in step S2, the temperature is raised to 600-700°C at 3-5°C / min, and the insulation time is 5-8h.
[0018] In addition, the present invention also provides a sodium manganese iron pyrophosphate composite material, which is prepared by the above preparation method.
[0019] In addition, the present invention also proposes a sodium manganese iron pyrophosphate composite material prepared by the above preparation method or the use of the above sodium manganese iron pyrophosphate composite material as a positive electrode material in preparing a battery.
[0020] Compared with the prior art, the beneficial effects of the present invention include: the preparation method of the sodium manganese iron pyrophosphate composite material proposed by the present invention includes: S1, mixing and stirring the sodium manganese iron pyrophosphate positive electrode material, the trivalent transition metal salt and the solvent to obtain a mixed slurry; S2, drying the mixed slurry to obtain a powder, and then heating the powder to 600-700°C in a hydrogen-argon mixed gas atmosphere to obtain the sodium manganese iron pyrophosphate composite material. By introducing the trivalent transition metal element in the trivalent transition metal salt during the sintering process, the trivalent transition metal element will occupy part of the area, so that the divalent transition metal element in NMFPP is enriched toward other areas, so that the element ratio of Na:TM:P in the partially enriched area changes from the original 4:3:4 to 4:4:4, that is, NaTMPO4 (TM=Fe, Mn) is generated. It is verified by XRD that the generated new phase is NaFePO4, so far, a sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material is obtained. The composite material prepared by this method can not only effectively solve the problems of unstable phase change of sodium iron manganese pyrophosphate material itself, dissolution of transition metal manganese during the cycle and poor structural stability, but also has a higher discharge specific capacity when used as a positive electrode material of the battery. At the same time, because sodium iron phosphate has an excellent theoretical capacity, it will not only not cause the electrochemical capacity of the composite material to decrease, but on the contrary can provide considerable capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Na4Mn prepared in Example 1 1.5 Fe 1.5 Microscopic morphology of (PO4)2(P2O7)@NaFePO4 sodium-ion battery composite material.
[0022] Figure 2 The Na4Mn prepared in Example 1 1.5 Fe 1.5 X-ray diffraction (XRD) pattern of (PO4)2(P2O7)@NaFePO4 sodium-ion battery composite material.
[0023] Figure 3 Na4Mn prepared in Example 1 and Comparative Example 1 1.5 Fe 1.5 Charge and discharge curves of (PO4)2(P2O7)@NaFePO4 sodium-ion battery composite material.
[0024] Figure 4 Na4Mn prepared in Example 1 and Comparative Example 1 1.5Fe 1.5 Charge and discharge cycle diagram of (PO4)2(P2O7)@NaFePO4 sodium-ion battery composite material. DETAILED DESCRIPTION
[0025] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0026] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0027] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0028] This specific embodiment provides a method for preparing a sodium manganese iron pyrophosphate composite material, comprising the following steps:
[0029] S1, mixing and stirring the sodium manganese iron pyrophosphate positive electrode material, a trivalent transition metal salt, and a solvent to obtain a mixed slurry; the trivalent transition metal salt is one or more of aluminum nitrate, lanthanum nitrate, and cerium nitrate; the solvent is ethanol; the mixing and stirring speed is 300-400r / min, and the mixing and stirring time is 2-3h;
[0030] S2. Dry the mixed slurry to obtain powder, and then heat the powder to 600-700° C. at 3-5° C. / min in a hydrogen-argon mixed gas atmosphere and keep the temperature for 5-8 h to obtain the sodium manganese iron pyrophosphate composite material.
[0031] In some embodiments, the trivalent transition metal salt is a mixed metal salt of aluminum nitrate, lanthanum nitrate and cerium nitrate; the molar ratio of the aluminum nitrate, the lanthanum nitrate and the cerium nitrate is 1:(1-1.5):(1-1.5).
[0032] This specific embodiment also provides a sodium manganese iron pyrophosphate composite material, which is prepared by the above preparation method.
[0033] This specific embodiment also proposes a sodium manganese iron pyrophosphate composite material prepared by the above preparation method or the use of the above sodium manganese iron pyrophosphate composite material as a positive electrode material in preparing a battery.
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0035] In the present invention, reference is made to “some embodiments”, “this embodiment”, examples, etc., which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.
[0036] If similar descriptions of "first / second" appear in the application documents, the following instructions are added. In the following description, the terms "first\second\third" involved are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It can be understood that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.
[0037] In this embodiment, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, object A and / or object B may represent three situations: object A exists alone, object A and object B exist at the same time, and object B exists alone.
[0038] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0039] Example 1
[0040] This embodiment provides a sodium manganese iron pyrophosphate composite material, which is prepared by the following steps:
[0041] S1. Weigh 10 g of sodium manganese iron pyrophosphate positive electrode material and 0.01 mol of aluminum nitrate into a ball mill, add 20 ml of ethanol as a dispersing solvent, and stir at a speed of 400 r / min for 2 h to mix them evenly to obtain a mixed slurry.
[0042] S2. The mixed slurry is then placed in a vacuum freeze-dried state at -20°C for 10 hours to obtain a dry powder. The powder is heated to 650°C at a rate of 3°C / min in a hydrogen-argon mixed gas atmosphere and kept at this temperature for 8 hours. After cooling, a sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material is obtained.
[0043] The obtained sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material was subjected to SEM and XRD analysis. The analysis results are as follows Figure 1 and Figure 2 As shown by Figure 1 and 2 The successful preparation of the composite material can be demonstrated.
[0044] The sodium manganese iron pyrophosphate positive electrode material of this embodiment is prepared by the following steps:
[0045] (1) Preparation of sodium manganese iron pyrophosphate cathode material precursor
[0046] Weigh 0.075 mol of manganese monoxide, 0.025 mol of ferrosoferric oxide, 0.1 mol of sodium carbonate and 0.05 mol of glucose into a ball mill, and then add 70 ml of deionized water as a solvent. Stir thoroughly for 2 hours at a speed of 400 r / min to mix the slurry evenly. After the stirring is completed, 85% phosphoric acid is prepared into a 4 mol / L phosphoric acid solution, and 50 ml of phosphoric acid solution is measured with a measuring cylinder and added to the above ball mill. Stir thoroughly for 3 hours at a speed of 400 r / min again, and after it is mixed, transfer it to the hydrothermal reactor. Set the temperature during the hydrothermal reaction to 220°C and the reaction time to 10 hours. After it is cooled to room temperature, separate the solid and liquid by a vacuum filter, and then place the solid at -20°C for vacuum freeze-drying for 24 hours to obtain the sodium manganese iron pyrophosphate precursor;
[0047] (2) Preparation of sodium manganese iron pyrophosphate positive electrode material
[0048] The sodium manganese iron pyrophosphate precursor obtained in (1) is placed in a hydrogen-argon mixed gas atmosphere, heated from room temperature to 350°C at a heating rate of 2°C / min, kept warm for 2h, then heated to 550°C at a rate of 3°C / min, and then sintered for 8h. After cooling, the sodium manganese iron pyrophosphate positive electrode material is obtained.
[0049] The sodium iron phosphate in-situ coated sodium iron manganese pyrophosphate composite material prepared in Example 1 was used as the positive electrode material to prepare a battery, and the electrochemical performance test was carried out as follows:
[0050] Weigh 0.40g of the composite material of Example 1, add 0.05g of conductive agent SuperP and 0.05g of binder polyvinylidene fluoride (i.e. PVDF), grind thoroughly, add 5mL of N-methylpyrrolidone (i.e. NMP) to mix, slurry evenly and apply it on aluminum foil, then transfer to a 120℃ vacuum oven for drying to make a positive electrode. In an argon glove box, CR2032 button cells were assembled with a metal sodium sheet as the negative electrode, glass fiber as the diaphragm, and 1mol / LNaPF6 / propylene carbonate (PC) + 5% fluoroethylene carbonate (FEC) as the electrolyte; the battery was tested for its first charge and discharge capacity at a rate of 0.1C in the voltage range of 1.7 to 4.3V, and its cycle performance was tested at a rate of 1C. The test results are as follows: Figure 3 and Figure 4 At a rate of 0.1C, its first discharge capacity is 113.7mAh / g; the first cycle coulombic efficiency can reach 98.2%; and the capacity retention rate is 90.5% after 500 cycles at a rate of 1C.
[0051] The sodium manganese iron pyrophosphate positive electrode material prepared in Example 1 was used as the positive electrode material to prepare a battery, and the electrochemical performance test was carried out in the same steps as the electrochemical performance test method of the composite material in Example 1. At a rate of 0.1C, its first discharge specific capacity was 94.8mAh / g; the first cycle coulomb efficiency was only 86.5%; and the capacity retention rate after 500 cycles at a rate of 1C was 72.1%.
[0052] Example 2
[0053] This embodiment provides a sodium manganese iron pyrophosphate composite material, which is prepared by the following steps:
[0054] S1. Weigh 10 g of sodium manganese iron pyrophosphate positive electrode material and 0.008 mol of lanthanum nitrate in a ball mill, add 20 ml of ethanol as a dispersing solvent, and stir at a speed of 400 r / min for 2 h to mix them evenly to obtain a mixed slurry;
[0055] S2. The mixed slurry is then placed in a vacuum freeze-dried state at -20°C for 12 hours to obtain a dry powder. The powder is heated to 630°C at a rate of 3°C / min in a hydrogen-argon mixed gas atmosphere and kept at this temperature for 5 hours. After cooling, a sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material is obtained.
[0056] The sodium manganese iron pyrophosphate positive electrode material of this embodiment is prepared by the following steps:
[0057] (1) Preparation of sodium manganese iron pyrophosphate cathode material precursor
[0058] Weigh 0.08 mol of manganese monoxide, 0.02 mol of ferrosoferric oxide, 0.09 mol of sodium carbonate and 0.045 mol of glucose into a ball mill, and then add 90 ml of deionized water as a solvent. Stir thoroughly for 3 hours at a speed of 400 r / min to mix the slurry evenly. After the stirring is completed, 85% phosphoric acid is prepared into a 7 mol / L phosphoric acid solution, and 30 ml of phosphoric acid solution is measured with a measuring cylinder and added to the above ball mill. Stir thoroughly for 4 hours at a speed of 400 r / min again, and after it is mixed, transfer it to the hydrothermal reactor. Set the temperature during the hydrothermal reaction to 250°C and the reaction time to 12 hours. After it is cooled to room temperature, separate the solid and liquid by a vacuum filter, and then place the solid at -20°C for vacuum freeze drying for 18 hours to obtain the sodium manganese iron pyrophosphate precursor;
[0059] (2) Preparation of sodium manganese iron pyrophosphate positive electrode material
[0060] The sodium manganese iron pyrophosphate precursor obtained in (1) is placed in a hydrogen-argon mixed gas atmosphere, heated from room temperature to 350°C at a heating rate of 2°C / min, kept warm for 2h, then heated to 550°C at a rate of 3°C / min, and then sintered for 8h. After cooling, the sodium manganese iron pyrophosphate positive electrode material is obtained.
[0061] The sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material prepared in Example 2 was used as the positive electrode material to prepare a battery, and the electrochemical performance test was carried out in the same steps as in Example 1. At a rate of 0.1C, its first discharge specific capacity was 109.1mAh / g; the first cycle coulomb efficiency could reach 99.0%; and the capacity retention rate after 500 cycles at a rate of 1C was 84.1%.
[0062] Example 3
[0063] This embodiment provides a sodium manganese iron pyrophosphate composite material, which is prepared by the following steps:
[0064] S1. Weigh 10 g of sodium manganese iron pyrophosphate positive electrode material and 0.01 mol of cerium nitrate in a ball mill, add 20 ml of ethanol as a dispersing solvent, and stir at a speed of 300 r / min for 3 h to mix them evenly to obtain a mixed slurry.
[0065] S2. The mixed slurry is then placed in a vacuum freeze-dried state at -20°C for 10 hours to obtain a dry powder. The powder is heated to 650°C at a rate of 5°C / min in a hydrogen-argon mixed gas atmosphere and kept at this temperature for 6 hours. After cooling, a sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material is obtained.
[0066] The sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material prepared in Example 3 was used as the positive electrode material to prepare a battery, and the electrochemical performance test was carried out in the same steps as in Example 1. At a rate of 0.1C, its first discharge specific capacity was 112.5mAh / g; the first cycle coulomb efficiency was 98.6%; and the capacity retention rate after 500 cycles at a rate of 1C was 83.2%.
[0067] Example 4
[0068] This embodiment provides a sodium manganese iron pyrophosphate composite material, which is prepared by the following steps:
[0069] Weigh 10g of sodium manganese iron pyrophosphate positive electrode material, add 0.004mol of lanthanum nitrate, 0.004mol of aluminum nitrate and 0.004mol of cerium nitrate in a ball mill, and add 50ml of ethanol as a dispersing solvent, and stir it at a speed of 350r / min for 2h to mix it evenly. Then place the mixed slurry in a vacuum freeze-drying at -20℃ for 12h to obtain a dry powder. The powder is heated to 600℃ at a rate of 5℃ / min in a hydrogen-argon mixed gas atmosphere, and kept warm for 5h. After cooling, the sodium manganese iron pyrophosphate composite material coated with sodium iron phosphate in situ can be obtained.
[0070] The preparation method of the sodium manganese iron pyrophosphate positive electrode material of this embodiment is the same as that of Example 1.
[0071] The sodium iron phosphate in-situ coated sodium manganese iron pyrophosphate composite material prepared in Example 4 was used as the positive electrode material to prepare a battery, and the electrochemical performance test was carried out in the same steps as in Example 1. At a rate of 0.1C, its first discharge specific capacity was 119.2mAh / g; the first cycle coulomb efficiency could reach 99.7%; and the capacity retention rate after 500 cycles at a rate of 1C was 95.4%.
[0072] Comparative Example 1
[0073] This comparative example proposes a sodium manganese iron pyrophosphate positive electrode material, which is prepared by the following steps:
[0074] (1) Preparation of sodium manganese iron pyrophosphate cathode material precursor
[0075] Weigh 0.06mol of manganese monoxide, 0.03mol of ferrosoferric oxide, 0.11mol of sodium carbonate, 0.01mol of aluminum nitrate and 0.06mol of glucose into a ball mill, and then add 70ml of deionized water as a solvent. Stir thoroughly for 2h at a speed of 400r / min to mix the slurry evenly. After the stirring is completed, 85% phosphoric acid is prepared into a 4mol / L phosphoric acid solution, and 50ml of phosphoric acid solution is measured with a measuring cylinder and added to the above ball mill. Stir thoroughly for 3h at a speed of 400r / min again, and after it is mixed, transfer it to the hydrothermal reactor. Set the temperature during the hydrothermal reaction to 220℃, and the reaction time to 10h. After it is cooled to room temperature, separate the solid and liquid by a vacuum filter, and then place the solid at -20℃ for vacuum freeze drying for 24h to obtain a common aluminum-coated sodium manganese iron pyrophosphate precursor;
[0076] (2) Preparation of sodium manganese iron pyrophosphate positive electrode material
[0077] The common aluminum-coated sodium manganese iron pyrophosphate precursor obtained in (1) is placed in a hydrogen-argon mixed gas atmosphere, heated from room temperature to 350°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, then heated to 550°C at a rate of 3°C / min, and then sintered for 8 hours. After cooling, a common aluminum-coated sodium manganese iron pyrophosphate positive electrode material is obtained;
[0078] The sodium manganese iron pyrophosphate material prepared in Comparative Example 1 was used as the positive electrode material to prepare a battery, and the electrochemical performance test was carried out in the same steps as in Example 1. At a rate of 0.1C, its first discharge capacity was 92.5 mAh / g; the first cycle coulombic efficiency was only 84.1%; and the capacity retention rate was 70.9% after 500 cycles at a rate of 1C.
[0079] Table 1 Electrochemical performance test results of sodium iron manganese pyrophosphate positive electrode materials of Examples 1-4 and Comparative Example 1 and Example 1
[0080]
[0081] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a sodium ferromanganese pyrophosphate composite material, characterized in that: The following steps are involved: S1, mixing and stirring the sodium manganese iron pyrophosphate positive electrode material, a trivalent transition metal salt, and a solvent to obtain a mixed slurry; S2, drying the mixed slurry to obtain powder, and then heating the powder to 600-700° C. in a hydrogen-argon mixed gas atmosphere and keeping the temperature to obtain the sodium manganese iron pyrophosphate composite material.
2. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 1, wherein: In step S1, the material ratio of the sodium manganese iron pyrophosphate positive electrode material and the metal salt is 10g:(0.01-0.15)mol.
3. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 1, characterized in that: The trivalent transition metal salt is one or more of aluminum nitrate, lanthanum nitrate and cerium nitrate.
4. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 3, characterized in that: The trivalent transition metal salt is a mixed metal salt of aluminum nitrate, lanthanum nitrate and cerium nitrate.
5. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 4, characterized in that: The molar ratio of the aluminum nitrate, the lanthanum nitrate and the cerium nitrate is 1:(1-1.5):(1-1.5).
6. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 1, characterized in that: In step S1, the solvent is ethanol.
7. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 1, characterized in that: In step S1, the mixing speed is 300-400 r / min, and the mixing time is 2-3 h.
8. The method for preparing the sodium ferromanganese pyrophosphate composite material according to claim 1, characterized in that: In step S2, the temperature is raised to 600-700°C at 3-5°C / min, and the insulation time is 5-8h.
9. A sodium manganese iron pyrophosphate composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the sodium manganese iron pyrophosphate composite material obtained by the preparation method according to any one of claims 1 to 8 or the sodium manganese iron pyrophosphate composite material according to claim 9 as a positive electrode material in preparing a battery.